Palatal Harvesting Technique Modification for Better Control of the Connective Tissue Graft Dimensions - Reino,Danilo Maeda (2013)
Subepithelial connective tissue graft (SCTG) has been extensively used for a variety of clinical applications. However, the surgical procedure may not allow control of graft thickness. The purpose of this case series is to illustrate a modification to the single incision palatal harvesting technique in order to control the SCTG thickness without increasing patient discomfort. Fifty cases from thirty systemically and periodontally healthy patients with at least one multiple gingival recession were treated with coronally advanced flaps combined with a SCTG. The palatal area served as the donor site, from where a single perpendicular incision was made to obtain a full thickness flap. Next, 1-2 mm of the flap was elevated and dissected to obtain a partial thickness flap. The graft remained attached to the full-partial thickness flap. After determining the desired SCTG thickness, the graft was harvested from the palatal flap. The patients healed uneventfully at 7 days postoperatively and primary closure was obtained for all palatal donor sites. The SCTG length and width varied depending on the needs of each case, but the SCTG thickness was well controlled with only 0.24 mm standard deviation. The suggested modification granted control of the SCTG dimensions and achieved complete wound closure within a week.